Local heteroepitaxial growth to promote the selective growth orientation, crystallization and interband transition of sputtered NiO thin films. Issue 10 (11th February 2016) - Wang, Y.; Ghanbaja, J.; Bruyère, S.; Boulet, P.; Soldera, F.; Horwat, D.; Mücklich, F.; Pierson, J. F.
Abstract : The growth orientation of a NiO top layer is governed by that of a Cu2 O seed layer, independent of its deposition conditions. Abstract : The room temperature growth of highly <111> oriented sputtered NiO thin films on glass and silicon substrates previously covered with a <111> oriented Cu2 O film is reported. The results are compared to those obtained from single layer NiO thin films using the same deposition conditions. Electron microdiffraction analyses indicate that NiO columns are heteroepitaxially grown on the columns of a Cu2 O seed layer. The well-matched atomic configurations between the Cu atoms in the 111 planes of Cu2 O and the O atoms in the 111 planes of NiO may provide a strong driving force to promote this local heteroepitaxial growth. Such heteroepitaxial growth behavior in the columns can significantly improve crystallization. Moreover, valence electron energy loss spectroscopy has been employed to investigate the interband transition properties of the NiO films, which shows that the interband transition intensity can be tuned by this local heteroepitaxial growth.